Computational study and optimization of an inclined U-channel cooling system for triple conductive panels under magnetic field - Selimefendigil, Fatih; Öztop, Hakan Fehmi (Elsevier, 2025)
In order to maximize the efficacy of multiple component electronic systems or photovoltaic panels in multiple arrangements, thermal management and cooling system design become crucial. In the present work, a novel cooling system with U-shaped cooling channel for triple conductive panel system is considered under ternary nano-enhanced magnetic field effects while Galerkin weighed residual finite element method is used as the solution technique. The numerical investigation is carried out for various Hartmann numbers (Ha between 0 and 60), magnetic field inclination (between 0 and 90), side wall inclination of cooling cavity (between 0 and 30), and cavity expansion ratio (between 0.2 and 0.5). At the highest Ha value, panel Pn2 shows a temperature reduction of 52 degrees C for eta = 0, and an increase of roughly 24 degrees C for eta = 30. The best magnetic field inclination for the lowest surface temperature varies according to the panels and cooling channels used. The surface temperature variation is 2 degrees C, 114 degrees and 114 degrees C for panels Pn1, Pn2, and Pn3, when comparing the best and worst cases. expansion ratios increase, the average Nu generally drops in cooling channels with both flat (zeta = 0) and inclined (eta = 30) walls. Based on the first three objectives by using optimization with COBYLA, panels Pn1, Pn2, and Pn3 have minimum temperatures of 30.3 degrees C, 46.6 degrees C, and 41.4 degrees C, respectively. By utilizing different objectives, different panel surface temperatures and performance improvements are achieved.
Keywords: Multiple photovoltaic cooling; Magnetic field; Finite element method; U-shaped channel; Optimization; Ternary nanofluid